2020
DOI: 10.31332/lkw.v6i2.1938
|View full text |Cite
|
Sign up to set email alerts
|

Illocutionary Acts in Religious Discourse: The Pragmatics of Nouman Ali Khan’s Speeches

Abstract: The present inquiry is designed to investigate the use of illocutionary acts in Nouman Ali Khan’s speeches and to analyse the functions of the types of illocutionary acts from the speeches. The data were analysed by using the textual analysis and open coding from three speeches by Nouman Ali Khan in a seminar titled “When Muslims Works Together” at the Islamic Association of North Texas (IANT). They are classified into some categories based on Searle’s theory. The finding of this study showed that (1) there ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Moreover, Firdaus, Amelia, and Lailiyah (2019) have discovered a strong connection between an interviewee's trustworthiness and the types of illocutionary acts they use, and representative is the most common type of illocutionary act because it leads to a lot of less trustworthy words. Akmal, Fitriah, and Zafirah (2020) have also found that the most frequently uttered in Nouman Ali Khan's speeches is a representative speech act which is informing, stating, describing, reminding, and concluding, and they do not find any declarative utterance. The illocutionary act is also found by Baok, Jayantini, and Santika (2021), who have stated that the representative speech act is the most dominant in Hillary Clinton's speech which most of them are stating.…”
Section: Resultsmentioning
confidence: 96%
“…Moreover, Firdaus, Amelia, and Lailiyah (2019) have discovered a strong connection between an interviewee's trustworthiness and the types of illocutionary acts they use, and representative is the most common type of illocutionary act because it leads to a lot of less trustworthy words. Akmal, Fitriah, and Zafirah (2020) have also found that the most frequently uttered in Nouman Ali Khan's speeches is a representative speech act which is informing, stating, describing, reminding, and concluding, and they do not find any declarative utterance. The illocutionary act is also found by Baok, Jayantini, and Santika (2021), who have stated that the representative speech act is the most dominant in Hillary Clinton's speech which most of them are stating.…”
Section: Resultsmentioning
confidence: 96%
“…DSA are also important speech acts as can be seen in the study conducted by Akmal et al (2020). DSA are an aspect of pragmatic discussion.…”
Section: Introductionmentioning
confidence: 93%
“…Pragmatics can encourage language learners and users to be competent in communicating (Akmal, Fitriah, & Zafirah, 2020) since it is used to examine a contextual meaning in an utterance. Therefore, contextual meaning becomes an important aspect of communication examined in this study.…”
Section: Introductionmentioning
confidence: 99%